ASUHAN KEPERAWATAN KELUARGA KOMBINASI KOMPRES HANGAT DAN RELAKSASI NAFAS DALAM MENGATASI NYERI HIPERTENSI - Dian Eka Kurniawati; Suri Salmiyati (Universitas Muhammadiyah Ponorogo, 2026)
Hypertension remains a critical global health challenge, directly contributing to cardiovascular morbidity and persistent symptoms such as neck pain due to vasoconstriction, which increases intracranial pressure and impairs quality of life. In Indonesia, low medication adherence and limited access to non-pharmacological management exacerbate this condition. This case study implemented family-centered nursing care, integrating non-pharmacological strategies to reduce pain and improve treatment adherence in uncontrolled hypertensive adults in Pasutan Hamlet, Bantul. Methods: This case study implemented family-centered nursing care that integrated non-pharmacological strategies to reduce pain and improve treatment adherence in adults with uncontrolled hypertension in Pasutan Hamlet, Bantul. The intervention focused on Mrs. S (51 years old). Data were collected through in-depth interviews, participatory observation, and physical examinations over three days (November 19–21, 2025), following a standard nursing process. The nursing diagnoses identified were Acute Pain and Risk-Prone Health Behavior. Implementation (November 22–24, 2025) included: (1) combined non-pharmacological therapy—warm neck compresses once daily for 10–15 minutes and deep breathing relaxation training for 15 minutes during pain episodes, and (2) health education on antihypertensive medication adherence. Evaluation on the third day showed significant outcomes: pain intensity decreased from 5 to 1 on the numeric scale, blood pressure improved from 143/92 mmHg to 128/84 mmHg, and the patient demonstrated greater independence in applying non-pharmacological techniques and stronger commitment to regular medication use. Family-centered nursing emphasizing education and combined warm compress and breathing relaxation therapy proved effective in reducing pain, controlling blood pressure, and enhancing self-management in hypertensive patients. Keywords: Family nursing care, hypertension, neck pain, warm compress, deep breathing relaxation